Local recurrence after surgery for locally advanced rectal cancer treated with or without preoperative chemoradiotherapy - Đurić, Mladen; Lukić, Dejan; Radovanović, Zoran; Đermanović, Aleksandar; Ranisavljević, Milan; Gutić, Bojana (Archive of Oncology, 2019)
Introduction: The ²gold standard² for patients with locally advanced rectal cancer is neoadjuvant chemoradiotherapy followed by surgery.Aim: Evaluation of local recurrence after surgery for locally advanced rectal cancer.Methods and patients: Retrospective study included 189 patients, who were operated at Oncology Institute of Vojvodina from January 1st 2012 until December 31st 2017. Patients were divided into two groups. In the first group 73 patients who received chemoradiotherapy were included, while 116 patients without neoadjuvant treatment were in the second group. All patients were diagnosed with locally advanced rectal cancer. The existence of operable metastases in the liver and/or lungs did not exclude patients from the study. Patients who had undergone resection of the rectum by Miles, Hartmann or local tumor excision were excluded from the study.Results: The median follow-up period was 48 months (range 13-84). In total, 23 (12.2%) patients developed local recurrence. In the chemoradiotherapy group, 15.1% (11 of 73 patients) had a local recurrence, as compared with 10.3% (12 of 116 patients) in the group without neoadjuvant treatment. In both groups, there were no correlation between  rate of local recurrence with other clinical and pathological parameters such as gender, tumor location, T and N stage, histological differentiation, or lymphovascular and perineural invasion (p>0.05). We confirmed significant association between circumferential resection margin with local recurrence in patients who were treated by preoperative chemoradiation (p=0.014).Conclusion: This study has not shown reduced risk of local recurrence after neoadjuvant therapy most likely due to small number of patients. Despite our results, neoadjuvant treatment followed by surgery remains the best treatment protocol for patients with locally advanced rectal cancer.
Keywords: Total mesorectal excision; Rectal cancer; Recurrence